THE EFFECT OF JOB SATISFACTION AND WORKLOAD ON EMPLOYEES PERFORMANCE OF PT BANK TABUNGAN NEGARA (BTN) SYARIAH PEKANBARU - Cengiz Kayacilar; R. Rudi Alhempi; Mulyani Rodi Muin; Muhammad Fahrozi; Budi Alamsyah Siregar (PENANOMICS: International Journal of Economics, 2022)
This study was conducted to determine the effect of job satisfaction and workload on the performance of employees of PT. State Savings Bank Syariah Branch Office Pekanbaru. The method used in this study is a descriptive method with a quantitative approach. The object of this research is all employees of PT Bank Tabungan Negara (BTN) Syariah Pekanbaru. The research location was conducted at PT Bank Tabungan Negara (BTN) Syariah Pekanbaru. The population in this study were employees of PT Bank Tabungan Negara Syariah Pekanbaru. The sample taken in this study were 47 respondents. The sampling technique in this study is the census method technique with data analysis using the SPSS version 20 program using validity test, reliability test, multiple linear regression, partial test (t test), simultaneous test (F test), coefficient of determination (R2) . Multiple regression analysis was used to test the hypothesis of this study. The results of the study stated that the variables of workload and job satisfaction had a significant effect simultaneously on employee performance. And it can be concluded that the most dominant workload variable affects employee performance. The value of the coefficient of determination (R 2) is 0.876. This means that the variables of job satisfaction and workload simultaneously affect employee performance variables by 87.6%.